Retrospective Analysis of the Treatment of Patients with Pain in Osteochondrosis of the Thoracic Spine - Kudrin, A.P. (TERRA ORTHOPAEDICA, 2022)
Summary. The purpose of this study was to identify signs of cardiac component in the development of chronic pain in osteochondrosis of the thoracic spine.Materials and Methods. Case histories of 434 patients with osteochondrosis of the thoracic spine who underwent examination and treatment in the SI “Institute of Traumatology and Orthopedics of NAMS of Ukraine” were retrospectively studied. Among them were 207 males and 227 females. The materials of inpatient and outpatient medical histories and consultative conclusions were processed. The place of residence, lifestyle of patients, the presence of concomitant pathology, duration of the disease, and the frequency of exacerbations per year were analyzed. Risk factors and complaints of patients with a careful emphasis on the nature of the pain syndrome were studied. The results of treatment were evaluated.Results. Males (47.7±2.4%) and females (52.3±2.3%) of working age (89.0%) suffered from thoracic osteochondrosis almost equally. The vast majority lived in cities (88.2%). Isolated thoracic osteochondrosis (43.3±0.3%) with the duration of the disease up to 1 year (72.3%) and the frequency of exacerbations once a year (54.4%) was the most common according to localization. The pain was mainly aching in nature with irradiation to the right half of the chest and right upper extremity (88.5%). The dependence of the pain syndrome on changes in body position and duration over time from one hour to several days was observed (92.1%). Risk factors for the development of the disease include hypodynamia (10.4%), obesity (5.5%), other comorbidities (4.6%), as well as genetic predisposition and bad habits (4.1% and 3%, respectively). In 90.0% of cases, the patients received drug treatment – nonsteroidal anti-inflammatory drugs (NSAIDs) and analgesics. 10.0% were treated with physiotherapy (52.7%), massage (97.2%), and therapeutic gymnastics (91.7%). 63.2% of patients were treated using a combination of medical and non-medical methods. According to the outcomes of treatment, a positive effect was noted in 87.5% of patients.Conclusions. Careful analysis of the negative outcomes indicates the presence in this category of patients probable concomitant cardiac pathology, which requires further study and examination.